2009
DOI: 10.1111/j.1365-246x.2009.04233.x
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters and rupture velocity of smallM≤ 2.1 reservoir induced earthquakes

Abstract: S U M M A R YWe calculate stress drop and rupture speed for M L ≤ 2.1 shallow reservoir induced earthquakes and find them to be similar to those of large, natural earthquakes. Previous studies have suggested that hydrofractures, mining and reservoir-induced earthquakes have lower average stress drop than natural tectonic earthquakes. This difference might result from the different tectonic setting or the shallower hypocentral depths of induced earthquakes. Alternatively, difficulties in correcting for attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 51 publications
(94 reference statements)
3
66
0
Order By: Relevance
“…Rupture velocity is limited by the Rayleigh wave velocity for subshear rupture speeds, suggesting that rupture velocity is some fraction of the shear wave speed. Although observations suggest a wide range of values, typical values for shallow earthquakes range from V r ≈ (0.6-0.9) [Freund, 1979;Imanishi et al, 2004;Kanamori and Brodsky, 2004;Yamada et al, 2005aYamada et al, , 2005bTomic et al, 2006;Dreger et al, 2007]. Therefore, if f 0 ∝ 1∕ and = r∕V r , it follows that f 0 is proportional to the shear wave velocity, assuming that rise time is significantly shorter than rupture time [Heaton, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture velocity is limited by the Rayleigh wave velocity for subshear rupture speeds, suggesting that rupture velocity is some fraction of the shear wave speed. Although observations suggest a wide range of values, typical values for shallow earthquakes range from V r ≈ (0.6-0.9) [Freund, 1979;Imanishi et al, 2004;Kanamori and Brodsky, 2004;Yamada et al, 2005aYamada et al, , 2005bTomic et al, 2006;Dreger et al, 2007]. Therefore, if f 0 ∝ 1∕ and = r∕V r , it follows that f 0 is proportional to the shear wave velocity, assuming that rise time is significantly shorter than rupture time [Heaton, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Goertz- Allmann et al (2011) analyzed stress drops of earthquakes induced by a waterinjection experiment into a borehole and obtained a clear increase in the stress drop as a function of distance from the injection point, thus suggesting that the stress drop correlates with pore pressure perturbations due to the injection. Tomic et al (2009) estimated stress drops of reservoir-induced earthquakes with M ≤ 2.1 and concluded that the values were similar to those of natural earthquakes. They speculated that the reservoirinduced earthquakes they had analyzed were intraplate earthquakes in the fresh rock and these showed higher stress drops than the values of other fluidinduced earthquakes.…”
Section: Studies On Seismicity and Stress Dropmentioning
confidence: 94%
“…Seismologists use quality factor (Q) to invert earthquake source properties (e.g., Tomic et al, 2009), characterize medium in a reservoir (Aki et al, 1982;Klimentos, 1995), etc. Attenuation determines detectability of perforations and microseismic events in microseismic monitoring (e.g., Einspigel and Eisner, 2014).…”
Section: Introductionmentioning
confidence: 99%